IGF‐1 promotes angiogenesis in endothelial cells/adipose‐derived stem cells co‐culture system with activation of PI3K/Akt signal pathway. (27th September 2017) - Lin, Shiyu; Zhang, Qi; Shao, Xiaoru; Zhang, Tao; Xue, Changyue; Shi, Sirong; Zhao, Dan; Lin, Yunfeng
Abstract: Objectives: The aim of this study was to investigate the role of insulin‐like growth factor‐1 (IGF‐1) and crosstalk between endothelial cells (ECs) and adipose‐derived stem cells (ASCs) in the process of angiogenesis. Methods: A three‐dimensional collagen gel used to culture mouse ASCs and mouse ECs in vitro was established. The effects of angiogenesis after exposure to IGF‐1 were observed by confocal laser scanning microscopy. Western blotting and qPCR were performed to elucidate the underlying mechanisms. Results: IGF‐1 treatment promoted the formation of vessel‐like structures and the recruitment of ASCs in the three‐dimensional collagen gel. The angiogenic genes and proteins in ECs were up‐regulated by IGF‐1 and in co‐culture. Similar changes in the genes and in the proteins were detected in ASCs after exposure to IGF‐1 and co‐culture. p‐Akt expression levels were high in ECs and ASCs after exposure to IGF‐1 and co‐culture. Conclusions: IGF‐1 and co‐culture between cells facilitate the process of angiogenesis via the PI3‐kinase/Akt signalling pathway. In ECs, IGF‐1 stimulates the expression of angiogenesis‐related growth factors with the activation of the PI3‐kinase/Akt signalling pathway. Co‐cultured ECs exposed to excess VEGF‐A and other angiogenesis‐related growth factors para‐secreted from ASCs exhibit high expression of angiogenesis‐related genes and proteins. In ASCs, IGF‐1 induces the recruitment and function of ASCs by up‐regulating the expression of PDGFB, MMPs and α ‐SMA . Crosstalk with ECs further facilitates changes in ASCs.